2021
DOI: 10.1155/2021/3910291
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dental Photography: Professional vs. Smartphone’s Camera

Abstract: There is a scant literature on the accuracy of dental photographs captured by Digital Single-Lens Reflex (DSLR) and smartphone cameras. The aim was to compare linear measurements of plaster models photographed with DSLR and smartphone’s camera with digital models. Thirty maxillary casts were prepared. Vertical and horizontal reference lines were marked on each tooth, with exception to molars. Then, models were scanned with the TRIOS 3 Basic intraoral dental scanner (control). Six photographs were captured for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The percentage of dentists trusting the use of their smartphone cameras instead of professional DSLR cameras is rising exponentially because of the former's easy access and manipulation [63].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of dentists trusting the use of their smartphone cameras instead of professional DSLR cameras is rising exponentially because of the former's easy access and manipulation [63].…”
Section: Discussionmentioning
confidence: 99%
“…In regards to the comparison between intraoral scanning and photograph, previous studies have conducted direct comparisons by comparing screenshots of anterior dental views obtained through intraoral scanning with frontal photographs taken by a DSLR camera. These studies have found no statistically significant differences in the lengths and widths of the maxillary anterior teeth [ 36 ]. As in the study done by Ahmed et al, the 3D measurement of mesiodistal widths of upper anterior teeth was done by measuring contact point from the facial side and the result had significant difference with the measurement on the photos [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this light, digital dentistry has led to the development of many innovative technologies that can aid the dentist in communicating with the patient; for example, the spread of digital technology has simplified the step of creating a set of facial and intraoral photographs, both in the production phase of the images and in their archiving. In addition to communication purposes, this allows the dentist to analyse the patient even after the actual visit, exchanging information with the dental laboratory and with colleagues who may participate in the execution of the therapies [57]. Currently, different devices can be used to improve such patient-operator communication, as diagnostic and virtual wax-up allow for the visualization of the possible prosthetic treatment.…”
Section: Dentist-patient Communication Toolsmentioning
confidence: 99%